Blood Superoxide Dismutase and Catalase Activities in Women Affected with Breast Cancer - M Negahdar; M Djalali; H Abtahi; MR Sadeghi; T Aghvami; E Javadi; H Layegh (Tehran University of Medical Sciences, 2005)
Experimental and epidemiological evidences implicate the involvement of oxygen derived radicals in the pathogenesis of cancer development. Oxygen derived radicals are able to cause damage to membranes, mitochondria and macromolecules including proteins, lipids and DNA. Accumulation of DNA damages has been suggested to contribute to carcinogenesis. It would, therefore, be advantageous to pinpoint the effects of oxygen derived radicals in cancer development. We investigated superoxide dismutase (SOD) and Catalase (CAT) activities in the whole blood of 50 breast cancer (BC) patients and 50 healthy and age matched women. The rate of SOD and CAT activities in BC patients was significantly lower (P<0.001) than controls. No effect of stage on SOD and CAT activities was observed. The results of our study have shown a higher reactive oxygen species (ROS) production and decreased SOD and CAT activities, which support the oxidative stress hypothesis in carcinogenesis. The relative lower SOD and CAT activities may not be adequate to detoxify high levels of H2O2 into H2O leading to the formation of the most dangerous 0OH radical. Therefore, administration of antioxidants may be helpful in the management of BC patients. However, elaborate clinical studies are required to evaluate the role of such antioxidant enzymes (AOE) in BC management.